Oogenesis in mammals - Clarke, Hugh (Henry Stewart Talks, 2019)
Oogenesis before birth, Phases of oogenesis: prenatal and postnatal, Oocyte and follicular growth, Role of granulosa cells, thecal cells, zona pellucida and transzonal projections in oocyte growth, FSH and follicular atresia, Meiotic progression during maturation, Role of LH, cyclic AMP, CDK and the follicular environment in oocyte maturation, Cytoplasmic maturation